Photoprocesses in Bis-Diethylamino Derivatives of 1,4- and 1,3-Distyrylbenzene - Atabekyan, Levon S.; Avakyan, Vitaly G.; Fomina, Marina V.; Nuriev, Vyacheslav N.; Medved’ko, Alexey V.; Vatsadze, Sergey Z.; Gromov, Sergey P.; Chibisov, Alexander K. (Molecules (Basel, Switzerland), 2024)
The photoprocesses of diethylamino derivatives of 1,4- and 1,3-distyrylbenzenes in MeCN were studied using absorption, luminescence, 1H NMR, and laser kinetic spectroscopy. Compounds 1 and 2 undergo intersystem crossing to the triplet state and exhibit delayed fluorescence. It was concluded that dye radical anions and radical cations are formed upon dismutation of the triplet state in the presence of an electron donor or acceptor. Quantum mechanical calculations for the structures of diethylamino distyrylbenzenes in the ground and excited states were carried out, making it possible to establish the structures of isomers and the most stable conformers for both compounds.